2017
DOI: 10.1080/02701367.2017.1377485
|View full text |Cite
|
Sign up to set email alerts
|

The Intersections of Science and Practice: Examples From FitnessGram® Programming

Abstract: The FitnessGram® program has provided teachers with practical tools to enhance physical education programming. A key to the success of the program has been the systematic application of science to practice. Strong research methods have been used to develop assessments and standards for use in physical education, but consideration has also been given to ensure that programming meets the needs of teachers, students, parents, and other stakeholders. This essay summarizes some of these complex and nuanced intersec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As a PRN, it is designed to provide mutual benefits through (Welk, Bai, Saint-Maurice, Allums-Featherston, & Candelaria, 2016) and provided a model for the more localized Iowa FitnessGram Initiative. The goal was to promote bilateral communications between researchers and practitioners for sustained collaborations, leading to a harmonious integration of science and practice (Welk, 2017). It proved to be a particularly useful setting to distribute the refined EB education module for evaluation in this study.…”
Section: Description Of the Iowa Fitnessgram Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…As a PRN, it is designed to provide mutual benefits through (Welk, Bai, Saint-Maurice, Allums-Featherston, & Candelaria, 2016) and provided a model for the more localized Iowa FitnessGram Initiative. The goal was to promote bilateral communications between researchers and practitioners for sustained collaborations, leading to a harmonious integration of science and practice (Welk, 2017). It proved to be a particularly useful setting to distribute the refined EB education module for evaluation in this study.…”
Section: Description Of the Iowa Fitnessgram Initiativementioning
confidence: 99%
“…A recent review found that only a small percentage of the health interventions have systematically examined effectiveness, adoption, implementation, and maintenance, which has slowed down the speed of their translation to dissemination for large practical impact (Green & Nasser, 2012). Additional research examining the dissemination and implementation of interventions is critical to promote the translation of science into practice (Green & Nasser, 2012;Welk, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A special curriculum area related to this could be fitness education, which offers the opportunity to acquire knowledge and understanding of fitness and healthy lifestyle habits. 33 , 34 It helps to develop the skills of short- and long-term planning and goal setting, measuring and self-tracking by building various fitness programmes, health-related exercises and sports activities. Unfortunately, this curriculum area is marginalized in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…The FitnessGram® assessmentin many places across the U.S. (e.g. NYC, Texas)is one of those policies, outwardly grounded in 'science' (Welk, 2017) and supported by strong ties to corporate, non-profit and government sectors (Gard & Pluim, 2017;Pluim & Gard, 2018). Pluim and Gard (2018) call the lack of critical scholarship and academic silence around Fitness-Gram® 'puzzling' (p. 275).…”
Section: Moving Towards Something New?mentioning
confidence: 99%